Implementation of the Probing Prompting Method in Islamic Religious Education Subjects at SMAN 1, South Halmahera Regency - Fitrianto, Arif Rahman (Civiliza Publishing, Indonesia., 2025)
The application of Probing Prompting in Islamic Religious Education is one solution in the approach to religious learning. This approach becomes interesting when open-mindedness is implemented in a religious context. The purpose of this study is to examine the application of the Probing Prompting Method in Islamic Religious Education subjects in high schools. The method used in this study is a qualitative descriptive approach. Data were collected through observation, documentation, and interviews, which were then analyzed using analytical descriptive methods. The data were then analyzed to draw conclusions. The results of this study can be concluded that the probing prompting approach in Islamic Religious Education at SMAN 1, South Halmahera Regency, was implemented through nine steps: preparation, delivering guiding questions, formulating questions and student answers, teacher assessment and responses, student assumptions, conclusions and summaries, practice questions, evaluation, motivation, and closing.